Allelic Variation and Distribution of the Major Maturity Genes in Different Soybean Collections - Miladinović, Jegor; Ćeran, Marina; Đorđević, Vuk; Balešević-Tubić, Svetlana; Petrović, Kristina; Đukić, Vojin; Miladinović, Dragana (Frontiers in Plant Science, 2018)
Soybean time of flowering and maturity are genetically controlled by E genes. Different allelic combinations of these genes determine soybean adaptation to a certain latitude. In this paper, we have described the first attempt to assess adaptation of soybean genotypes developed and realised at Institute of Field and Vegetable Crops, Novi Sad, Serbia (Novi Sad (NS) varieties and breeding lines) based on E gene variation, as well as to comparatively assess E gene variation in North-American (NA), Chinese and European genotypes, as most of the studies published so far are dealing only with North-American and Chinese cultivars and breeding material. Allelic variation and distribution of the major maturity genes (E1, E2, E3 and E4) has been determined in 445 genotypes from soybean collections of NA ancestral lines, Chinese germplasm, European varieties, and NS varieties and breeding lines. The study showed that allelic combinations of E1-E4 genes significantly determined the adaptation of varieties to different geographical regions, although they have different impacts on maturity. In general, each collection had one major E genotype haplogroup, comprising over 50% of the lines. The exceptions were European varieties that had two predominant haplogroups and NA ancestral lines that were distributed almost evenly among several haplogroups. As e1-as/e2/E3/E4 was the most common genotype in NS population, and was present in the top yield performing genotypes, this specific allele combination was proposed as optimal for the environments of Central-Eastern Europe.